2022
DOI: 10.1177/00369330221078993
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Integrated bioinformatic analysis of key biomarkers and signalling pathways in psoriasis

Abstract: Background and Aims Psoriasis is a relatively common autoimmune inflammatory skin disease with a chronic etiology. Since psoriasis is still incurable, it is necessary to identify the molecular mechanisms of psoriasis. The present study was designed to detect novel biomarkers and pathways associated with psoriasis incidence, and provide new insights into treatment of psoriasis. Methods and Results Differentially expressed genes (DEGs) associated with psoriasis in the Gene Expression Omnibus (GEO) database were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
6
2
0
Order By: Relevance
“…Tang et al. reported that cytokine‐cytokine receptor interaction, viral protein interaction with cytokine and cytokine receptor, IL‐17 signaling pathway and NOD‐like receptor signaling pathway were significantly enriched in psoriasis, 45 which is consistent with our results. Among them, the IL‐17 signaling pathway is considered to be one of the pathways most closely related to the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tang et al. reported that cytokine‐cytokine receptor interaction, viral protein interaction with cytokine and cytokine receptor, IL‐17 signaling pathway and NOD‐like receptor signaling pathway were significantly enriched in psoriasis, 45 which is consistent with our results. Among them, the IL‐17 signaling pathway is considered to be one of the pathways most closely related to the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these genes may serve as biomarkers for detecting covert UC in psoriasis patients GO and KEGG analyses showed the common DEGs were highly related with immune response, indicating immune response played a pivotal role in the initiation of psoriasis and UC. Tang et al reported that cytokine-cytokine receptor interaction, viral protein interaction with cytokine and cytokine receptor, IL-17 signaling pathway and NOD-like receptor signaling pathway were significantly enriched in psoriasis, 45 which is consistent with our results. Among them, the IL-17 signaling pathway is considered to be one of the pathways most closely related to the pathogenesis of psoriasis.…”
Section: Shokrollah Et Al Have Shed Light On Potential Novel Biomarke...supporting
confidence: 93%
“…OAS1 is a member of OASs (2′−5′oligoadenylate synthetases) family, which also contains OAS2, OAS3, and OASL, being IFN-induced enzymes with multiple antiviral activities. The overexpression of OAS1 in psoriasis and low expression after biologics were revealed in some researches, 34,35 accordant with ours.…”
Section: Discussionsupporting
confidence: 87%
“…As members of IFIT (IFN‐γ stimulated genes) family, IFIT1 and IFIT3 may act as a regulator of anti‐inflammatory and immune responses 29,30 . In some researches, IFIT1 was identified low expression when interventions were used to suppress nonalcoholic hepatitis, 29,31 and the expression of IFIT1 and IFIT3 was validated as upregulated in psoriasis, 21,32–34 which was consistent with the high expression in both psoriasis and NASH we found. OAS1 is a member of OASs (2′−5′‐oligoadenylate synthetases) family, which also contains OAS2, OAS3, and OASL, being IFN‐induced enzymes with multiple antiviral activities.…”
Section: Discussionsupporting
confidence: 83%
“…In immune‐related diseases, IFIT3 can be a potential biomarker for pulmonary arterial hypertension‐associated systemic sclerosis 76 . IFIT3 has also been suggested as a potential gene or therapeutic target in myocardial infarction, 77,78 ankylosing spondylitis, 80 psoriasis, 81 atherosclerosis, and potentially other inflammatory diseases 79 . In cancer, IFIT3 may be a biomarker for ESCC 70 .…”
Section: Ifit3 As a Biomarker For Disease Diagnosis And Prognosismentioning
confidence: 99%